Treatment Outcome in Patients with Mycobacterium abscessus Complex Lung Disease: The Impact of Tigecycline and Amikacin - Jeng-How Yang; Ping-Huai Wang; Sheng-Wei Pan; Yu-Feng Wei; Chung-Yu Chen; Ho-Sheng Lee; Chin-Chung Shu; Ting-Shu Wu (MDPI AG, 2022)
Background: The contemporary guidelines have recommended multiple antimicrobial therapies along with oral macrolides for the treatment of Mycobacterium abscessus complex lung disease (MABC-LD). However, there is little evidence supporting the parenteral tigecycline-containing regimens against MABC-LD. Therefore, we conducted this study to evaluate the effect of intravenous tigecycline-containing regimens on the treatment of MABC-LD. Methods: A retrospective study was conducted in 6 medical centers. Patients with MABC-LD that were followed up at ≥12 months were enrolled. Mycobacterium abscessus subspecies were identified by hsp65, rpoB, secA1 gene PCR, and sequencing. Antimicrobial susceptibility was determined for 34 patients using broth microdilution methods following the Clinical and Laboratory Standards Institute (CLSI) guideline. The microbiology and treatment outcomes were defined as either success or failure. The impacts of tigecycline and amikacin were adjusted for age, comorbidities, surgical resection, and radiologic scores. Results: During the study period, seventy-one patients were enrolled for final analysis. The microbiology failure rate was 61% (43/71) and the treatment failure rate was 62% (44/71). For M. abscessus complex, 97% (33/34) of tigecycline MIC were ≤1 mg/L. Amikacin also demonstrated great susceptibility (94.1%; 32/34). Treatment with regimens containing tigecycline plus amikacin provided better microbiology success (adjusted OR 17.724; 95% CI 1.227-267.206) and treatment success (adjusted OR 14.085; 95% CI 1.103-166.667). Conclusion: The outcome of MABC-LD is always unsatisfactory. Treatment regimens with oral macrolide in combination with tigecycline and amikacin were correlated with increased microbiology success and less treatment failure.